Perkembangan Sound System sebagai Budaya dan Kompetisi Sosial di Desa Sumbersewu, Kecamatan Muncar, Banyuwangi - Allya Salsa Bilatul Kh; Diajeng Anugrah Cantika Sari; Fatkurohman Nur Rangga (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This research examines the dynamics of the use of sound systems as a cultural phenomenon and social competition in Sumbersewu Village, Banyuwangi. Using an ethnographic approach and Jean Baudrillard's concept of consumption society, this research explores the history of the emergence of sound systems and their evolution into an integral part of local community life. Focusing on the tradition of sound system fighting as the object of research. This research shows how the sound system has become a means of uniting young people in the village, while strengthening their cultural identity. Through direct data collection in the field, including observations and interviews with participants and local residents, this research describes how the sound system community in Sumbersewu Village organizes and prepares for sound system competition events, as well as how this influences social relations and the dynamics of local community life. The research results show that the use of sound systems not only reflects technological and cultural developments at the local level, but also plays a role in forming communities and strengthening social ties within them.